DAUR ULANG BOTOL BEKAS MENJADI PIGGY BANKS UNTUK MENGASAH KREATIVITAS DAN MEMOTIVASI SISWA UNTUK MENABUNG - Siti Ermawati; Taufiq Hidayat; Ima Isnaini Taufiqur Rohmah; Fitri Nurdianingsih; Ali Mujahidin (IKIP PGRI Bojonegoro, 2017)
The rubbish is the waste of goods that are not needed by the community. However, it does not mean that rubbish does not have any utility at all. Actually, used bottles can be recycled into a variety of creative products. Unfortunately, just a few people are willing to exploit the potential of the rubbish, so its existence becomes useless, and even just pollute the environment. This community service program aims to hone the creativity of students in recycling the bottles into unique piggy banks and improving students' movements to save their money. The method used in this program is Participatory Rural Appraisal (PRA). The participants are the students of class 5 SDN Prigi 1 (n=14). The steps of program implementation include; 1) counseling, 2) demonstration, 3) tools provision, 4) practice, and 5) evaluation. The results of the program are the partisipantâ€™s understanding and skill in recycling the bottles into unique and creative piggy banks. Some piggy bank products produced by participants include; a turtle-shaped pig, an owl, and a plane. Students are expected to be more motivated to save their from an early age.Keywords: Recycle, Used bottles, Piggy banksÂ ABSTRAKSampah merupakan sisa atau buangan dari barang yang tidak diperlukan oleh masyarakat. Meskipun demikian, bukan berarti sampah tidak memiliki kegunaan sama sekali. Botol bekas sebenarnya bisa didaur menjadi berbagai produk kreatif yang memiliki nilai guna dan nilai ekonomi. Persoalannya, sangat sedikit orang dapat mememanfaatkan potensi sampah sehingga keberadaannya menjadi sia-sia dan bahkan menjadi limbah yang mencemari lingkungan. PKM ini bertujuan untuk mengasah kreativitas siswa dalam mendaur ulang botol bekas menjadi Piggy Banks dan meningkatkan movitasi siswa untuk menabung. Metode yang digunakan dalam kegiatan PKM ini adalah Participatory Rural Appraisal (PRA). Peserta PKM terdiri dari siswa Kelas V SDN Prigi 1 yang berjumlah 14 Orang. Langkah-langkah pelaksanaan PKM meliputi; 1) penyuluhan, 2) demonstrasi, 3) pemberian bantuan alat, 4) praktek, dan 5) evaluasi. Hasil dari kegiatan PKM ini adalah pemahaman dan keterampilan siswa dalam mendaur ulang botol bekas menjadi piggy bank unik dan kreatif. Beberapa produk piggy bank yang dihasilkan siswa antara lain; piggy bank berbentuk kura-kura, burung hantu, dan pesawat. Dengan hasil ini, siswa diharapkan dapat lebih termotivasi untuk menabung sejak usia dini.Kata Kunci: Daur ulang, Botol bekas, Piggy banks